Peran Pelatihan Kewirausahaan dalam Peningkatan Sumber Daya Manusia di Desa Tanjung Glugur - hukmah, safiroh; Fahrudin (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
This study aims to examine the role of entrepreneurship training in improving human resource quality in Tanjung Glugur Village. A qualitative descriptive approach was employed to explore how training impacts technical skills, entrepreneurial mindset, and the empowerment of vulnerable groups, particularly persons with disabilities. The findings reveal that training based on experiential learning significantly enhances managerial capacity, creativity, and participants’ self-confidence. The training program is inclusive and adaptive, designed according to local needs and involving various stakeholders, including village governments and disability groups. The participatory approach implemented makes the training an effective empowerment tool for developing independent entrepreneurs. Beyond enhancing individual productivity, the program contributes to sustainable village economic growth. The success of the training is evident in the participants’ transformation before and after the program, both in terms of technical competencies and entrepreneurial mentality.